Cardiac remodelling in a baboon model of intrauterine growth restriction mimics accelerated ageing. (17th December 2016) - Kuo, Anderson H.; Li, Cun; Li, Jinqi; Huber, Hillary F.; Nathanielsz, Peter W.; Clarke, Geoffrey D.
Abstract : Key points: Rodent models of intrauterine growth restriction (IUGR) successfully identify mechanisms that can lead to short‐term and long‐term detrimental cardiomyopathies but differences between rodent and human cardiac physiology and placental‐fetal development indicate a need for models in precocial species for translation to human development. We developed a baboon model for IUGR studies using a moderate 30% global calorie restriction of pregnant mothers and used cardiac magnetic resonance imaging to evaluate offspring heart function in early adulthood. Impaired diastolic and systolic cardiac function was observed in IUGR offspring with differences between male and female subjects, compared to their respective controls. Aspects of cardiac impairment found in the IUGR offspring were similar to those found in normal controls in a geriatric cohort. Understanding early cardiac biomarkers of IUGR using non‐invasive imaging in this susceptible population, especially taking into account sexual dimorphisms, will aid recognition of the clinical presentation, development of biomarkers suitable for use in humans and management of treatment strategies. Abstract: Extensive rodent studies have shown that reduced perinatal nutrition programmes chronic cardiovascular disease. To enable translation to humans, we developed baboon offspring cohorts from mothers fed ad libitum (control) or 70% of the control ad libitum diet in pregnancy and lactation, which were growth restricted at birth. We hypothesized that intrauterine growth restriction (IUGR) offspring hearts would show impaired function and a premature ageing phenotype. We studied IUGR baboons (8 male, 8 female, 5.7 years), control offspring (8 male, 8 female, 5.6 years – human equivalent approximately 25 years), and normal elderly (OLD) baboons (6 male, 6 female, mean 15.9 years). Left ventricular (LV) morphology and systolic and diastolic function were evaluated with cardiac MRI and normalized to body surface area. Two‐way ANOVA by group and sex (with P < 0.05) indicated ejection fraction, 3D sphericity indices, cardiac index, normalized systolic volume, normalized LV wall thickness, and average filling rate differed by group. Group and sex differences were found for normalized LV wall thickening and normalized myocardial mass, without interactions. Normalized peak LV filling rate and diastolic sphericity index were not correlated in control but strongly correlated in OLD and IUGR baboons. IUGR programming in baboons produces myocardial remodelling, reduces systolic and diastolic function, and results in the emergence of a premature ageing phenotype in the heart. To our knowledge, this is the first demonstration of the specific characteristics of cardiac programming and early life functional decline with ageing in an IUGR non‐human primate model. Further studies across the life span will determine progression of cardiac dysfunction. Key points: Rodent models of intrauterine growth restriction (IUGR) successfully identify mechanisms that can lead to short‐term and long‐term detrimental cardiomyopathies but differences between rodent and human cardiac physiology and placental‐fetal development indicate a need for models in precocial species for translation to human development. We developed a baboon model for IUGR studies using a moderate 30% global calorie restriction of pregnant mothers and used cardiac magnetic resonance imaging to evaluate offspring heart function in early adulthood. Impaired diastolic and systolic cardiac function was observed in IUGR offspring with differences between male and female subjects, compared to their respective controls. Aspects of cardiac impairment found in the IUGR offspring were similar to those found in normal controls in a geriatric cohort. Understanding early cardiac biomarkers of IUGR using non‐invasive imaging in this susceptible population, especially taking into account sexual dimorphisms, will aid recognition of the clinical presentation, development of biomarkers suitable for use in humans and management of treatment strategies.